1991
DOI: 10.1007/bf00938040
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the attitudes and intentions of future professionals toward self‐help

Abstract: Examined the attitudes, beliefs, and intentions toward self-help groups of 168 graduate students in clinical psychology and social work from five universities using the theory of reasoned action as a model (Fishbein, 1979). Participants held positive attitudes and beliefs regarding self-help and intended to collaborate. Participants who were members of self-help groups had significantly greater intentions to collaborate and had more positive beliefs vs. nonmembers. There were no differences between social work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Second, this study focused on testing hypotheses about the predictor variables of social work inputs, changeinducing mechanisms, and mutual aid. This leaves room for the investigation of alternative models associated with factors such as social workers' training in mutual aid groups (Meissen et al, 1991), organizational affiliation and support (Kelly, 2003;Lotery and Jacobs, 1994), and adolescents' peer networks (Holland, Reynolds and Weller, 2007). Other means of extending this study may include launching a longitudinal study to examine the various stages of mutual aid and EBP alleviation among young people, and using in-depth interviews and focus groups to collect qualitative data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, this study focused on testing hypotheses about the predictor variables of social work inputs, changeinducing mechanisms, and mutual aid. This leaves room for the investigation of alternative models associated with factors such as social workers' training in mutual aid groups (Meissen et al, 1991), organizational affiliation and support (Kelly, 2003;Lotery and Jacobs, 1994), and adolescents' peer networks (Holland, Reynolds and Weller, 2007). Other means of extending this study may include launching a longitudinal study to examine the various stages of mutual aid and EBP alleviation among young people, and using in-depth interviews and focus groups to collect qualitative data.…”
Section: Discussionmentioning
confidence: 96%
“…These results are in line with those of previous studies. For instance, Meissen, Mason and Gleason (1991) noted that while members of different categories of mutual aid groups clearly face different situations personally, their reciprocal support needs are essentially the same among various categories of mutual aid groups. Similarly, Kurtz (2004), in a comparison of different mutual aid groups, found that the effects of different forms of mutual aid on members' rehabilitation and development were very much alike despite their different problem focuses, group sizes, and meeting formats.…”
Section: Discussionmentioning
confidence: 97%
“…Research consistently demonstrates that professionals evaluate self-help groups as helpful (e.g. Hermalin et al, 1979;Levy, 1978;Meissen et al, 1991;Todres, 1982). However, comparisons of professional perceptions of self-help groups relative to their perceptions of professionally-led groups indicates that professionally-led groups are routinely perceived as signi®cantly more helpful (Salzer et al, 1994), despite the lack of data in support of this perception (Christensen and Jacobson, 1994).…”
Section: Introductionmentioning
confidence: 93%
“…Whilst a majority of the existing TPB studies explore patient physical health-related behaviors, such as condom use (Albarracin et al, 2001), exercise habits (Courneya, 1995) and smoking (Godin, Valois, Lepage, & Desharnais, 1992), there are only a few studies that explore the application of TPB with mental health therapists' behaviors (Casper, 2007;Kelly, Deane, & Lovett, 2012;Klaybor, 1998;Meissen, Mason & Gleason, 1991). For instance, Klaybor's (1998) study of 249 social workers' intention to use the Diagnostic Statistical Manual, Fourth Edition (DSM-IV) for assessment and treatment purposes found that attitudes, subjective norms, and perceived behavioral control were significant predictors of behavioral intentions.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%